Effects of reproductive biology on heavy metal pollution on the histopathological structure of gonads in India - Mukesh Mehta Ambani (Advances in Aquaculture and Fisheries Management, 2015)
Water pollution caused by heavy metals affects breeding and development in fishes of Harike wetland. The effects of heavy metals on fishes are related to their uptake and accumulation by the organism, resulting in metal induced disturbances in the structures and functions of various tissues and organs. Early life stage of fish development, such as oocytes maturation is very sensitive to intoxication. Samples of the fish Labeo rohita were collected from the two sites to assess the effects of the water quality and concentrations of heavy metals on the fish ovary. The histopathological changes in gonads have been studied due to exposure of different pollutants. It was concluded that incidences of gonadal abnormalities in the form of deformed oocytes, reduction in their numbers and lack of active oogenesis have been observed. From the results it is inferred that wetland is passing through an alarming situation because deformities in early stages of oocytes have been observed. It is posing a serious threat to the biodiversity existing there. It is recommended that waste water discharge from various sources should be treated to protect the fish and the public health from the menace of pollution.